2018
DOI: 10.37358/mp.18.3.5034
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study on the Need for Postoperative Analgesic Medication After Surgical Treatment of Inguinal Hernia with Surgical Mesh through Laparoscopic or Classic Approach

Abstract: The incidence of postoperative pain in patients operated for inguinal hernia can reach up to 40% of cases, depending on different authors, and depending on the approach used in the surgical treatment of these patients. Currently, there are two commonly accepted ways of surgical treatment of inguinal hernias, the classic approach with polypropylene mesh (Liechtenstein technique) and the laparoscopic approach. The purpose of this study was to conduct a comparative analysis on the need for analgesic medication in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Most studies published in recent years have highlighted the importance of inflammatory syndrome in the pathogenesis of various cancers, including colorectal cancer [19]. It has also been demonstrated that the severity of the systemic inflammatory syndrome affects the prognostic of these patients [20][21][22]. At the same time, some authors have proven that chronic inflammatory syndrome stimulates the growth of malignant tumors as well as the metastatic process [23,24].…”
Section: Resultsmentioning
confidence: 99%
“…Most studies published in recent years have highlighted the importance of inflammatory syndrome in the pathogenesis of various cancers, including colorectal cancer [19]. It has also been demonstrated that the severity of the systemic inflammatory syndrome affects the prognostic of these patients [20][21][22]. At the same time, some authors have proven that chronic inflammatory syndrome stimulates the growth of malignant tumors as well as the metastatic process [23,24].…”
Section: Resultsmentioning
confidence: 99%
“…Patients with BCLC B-stage who benefit from TACE and another alternative therapy (eg, RFA) may be associated with or exhibit tumor stagnation, or tumor necrosis in most cases [26]. In C stages BCLC, desperate cases -the two patients to whom TACE was the last therapeutic attitude, despite the predicted prognosis, TACE assured the prolongation of life and increased life quality [27][28][29]. In the majority of patients in this study, stage A BCLC, chemoembolization was a therapeutic attitude that allowed subsequent liver transplantation (when it was not Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In this regard, there are studies in the literature that have shown that the existence of increased vascular permeability in the tumor before initiating neo-adjuvant radiochemotherapy is associated with a good therapeutic response, in these cases. Other authors have also shown that the existence of mucin at the level of the tumor formation is associated with a poor therapeutic response in these cases [84][85][86][87].…”
Section: Evaluation Of the Response To Neo-adjuvant Radiochemotherapymentioning
confidence: 99%